Development of gateway discovery and selection scheme for MANEMO (MGDSS) - Mahmod, Zainab S.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Anwar, Farhat; Hameed, Shihab A. (Science & Engineering Research Support Society, 2017)
To achieve the requirement of the improvement applications and guarantee the Internet access for mobile hosts and networks, the Internet Engineering Task Force (IETF) proposed Mobile Ad Hoc NEMO (MANEMO) architecture. However, the integration of NEMO and MANET introduces many challenges such as the redundant tunnel problem and Exit Router selection when multiple Exit Routers to the Internet exist. This paper aims to propose a scheme that discovers and selects the gateway which improves the performance and the robustness of the network regardless of routing protocol used. This is done by extending the Tree Discovery Protocol (TDP) used by NEMO BSP and the Neighborhood Discovery protocol used by MANET and the gateway selection is based on multiple criteria: the hop count, the nested level, the stable time and the number of nodes registered at the intermediate nodes. The OPNET Modeler 14.5 is used to evaluate the proposed scheme and compare its performance with the standard NEMO BSP and the Multi-homed MANEMO (M-MANEMO) approach. The results show that the average data packets dropped of the proposed scheme is 28.6% less compared to the NEMO BSP and 63% compared to the M-MANEMO. And in a larger scale MANEMO with high traffic load and fast mobility, the proposed scheme outperforms the M-MANEMO with reduced end-to-end delay around 21.6%. Whereas NEMO BSP has 68.7% more end-to-end delay in compare. These delays cause that the proposed scheme has 66.6% less voice jitter compared to M-MANEMO.